Mining Safety and Sustainability II - Dong, Longjun; Zhao, Yanlin; Chen, Wenxue (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Safety and sustainability are becoming ever bigger challenges for the mining industry with the increasing depth of mining. It is of great significance to reduce the disaster risk of mining accidents, enhance the safety of mining operations, and improve the efficiency and sustainability of development of mineral resource. This book provides a platform to present new research and recent advances in the safety and sustainability of mining. More specifically, Mining Safety and Sustainability presents recent theoretical and experimental studies with a focus on: safety mining, green mining, sustainable development, risk management of mines, mining methods and technologies, damage monitoring and prediction. It will be further helpful to provide theoretical support and technical support for guiding the normative, green, safe and sustainable development of the mining industry.